Peran Tokoh Agama dalam Membangun Moderasi Beragama di Kota Aek Nabara Kabupaten Labuhanbatu - Muktarruddin, Muktarruddin; Ritonga, Muhammad Husni (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This research aims to find out the role of religious figures in building religious moderation in the city of Aek Nabara, Labuhanbatu Regency. This research uses a qualitative approach. The research results explain that religion moderation in the city of Aek Nabara is local wisdom. The sociological and cultural ties between people of different religions in the city of Aek Nabara have been going on for a long time and there has never been any conflict between religions. There are six roles of religion figures in building religious moderation in the city of Aek Nabara. First, supporting the government in promoting religious moderation and national commitment. Second, informing and explaining the principles of religion moderation to the public. Third, building harmony between religious communities in the city of Aek Nabara. Fourth, caring for and building togetherness to build religious moderation. Fifth, remind the public to stay away from intolerant attitudes and sixth, be an example in implementing religious moderation for society and the ummah. The role of religious leaders makes the atmosphere of religious moderation in the city of Aek Nabara conducive.